Styl indywidualny dziennikarza radiowo-telewizyjnego Roberta Kantereita = Individual style of radio and television reporter Robert Kantereit - Tyc, Ewelina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the contemporary media, there is a fashion for individual distinctiveness and unrestrained self-expression. A great role is played by reporters who act as hosts of magazines. This article presents an analysis of the individual style of Robert Kantereit, who has been a recognized radio reporter and a face of the Polish television for 17 years. He combines audial skills that are important in the radio with vision that, in turn, is the domain of television. His person shows splendidly differences and similarities between the language of radio and the language of television.
Keywords: polska telewizja; polskie radio; styl indywidualny; polskie dziennikarstwo; dziennikarz radiowo-telewizyjny; magazyn radiowy; magazyn telewizyjny; Polish television; Polish radio; individual style; Polish journalism; radio and television reporter; television magazine; radio magazine